PANDANGAN ULAMA TERHADAP PEMBEDAHAN PLASTIK (Ahkam: Jurnal Hukum Islam, 2022)
Plastic surgery is an effective method and aims to realize the needs of consumers, especially in the face of the modern era. Although it is seen that its users give a positive impact, but as a Muslim who must adhere to Islamic law in all activities, a Muslim who performs plastic surgery should know the meaning and law of plastic surgery. Therefore, based on the Qur’an and hadith, muslim scholars give insights in their writings on changing the shape that this time can also be adapted to plastic surgery. The problem statement in this research is: what is mean and the law of plastic surgery in the view of Muslim scholars. While the objective of this research is to know the meaning and description of the law of plastic surgery in the view of muslim scholars. The methodology in this study uses the library method. From the point of view of the problem studied, this research uses an integrative, philosophical, systematic, and universal approach in order to find wisdom or facts about the research. The nature of this research is analytical descriptive. The methods of analysis that researchers use in this research are descriptive, comparative and critical analysis. The results of this study found that not all muslim scholars agree on the meaning of changing shape as a physical change. The muslim scholars who mean changing shape as a change in the physical, in general allows changing shape to reshape and prohibit changing shape to beautify.